Sodium dodecyl sulfate‐coated silver nanoparticles accelerate antimicrobial potentials by targeting amphiphilic membranes - Xiuyan Jin; Na Peng; Aoran Cui; Yue Liu; Xianqi Peng; Linlin Huang; Abdelaziz Ed‐Dra; Fang He; Yan Li; Shikuan Yang; Min Yue (mLife)
Abstract Compelling concerns about antimicrobial resistance and the emergence of multidrug‐resistant pathogens call for novel strategies to address these challenges. Nanoparticles show promising antimicrobial activities; however, their actions are hindered primarily by the bacterial hydrophilic–hydrophobic barrier. To overcome this, we developed a method of electrochemically anchoring sodium dodecyl sulfate (SDS) coatings onto silver nanoparticles (AgNPs), resulting in improved antimicrobial potency. We then investigated the antimicrobial mechanisms and developed therapeutic applications. We demonstrated SDS‐coated AgNPs with anomalous dispersive properties capable of dispersing in both polar and nonpolar solvents and, further, detected significantly higher bacteriostatic and bactericidal effects compared to silver ions (Ag+). Cellular assays suggested multipotent disruptions targeting the bacterial membrane, evidenced by increasing lactate dehydrogenase, protein and sugar leakage, and consistent with results from the transcriptomic analysis. Notably, the amphiphilic characteristics of the AgNPs maintained robust antibacterial activities for a year at various temperatures, indicating long‐term efficacy as a potential disinfectant. In a murine model, the AgNPs showed considerable biocompatibility and could alleviate fatal Salmonella infections. Collectively, by gaining amphiphilic properties from SDS, we offer novel AgNPs against bacterial infections combined with long‐term and cost‐effective strategies.